Gambaran pengetahuan pencegahan kekerasan pada perempuan di GMIM Viadolorosa, Manado - Sipayung, Evita Melinda; Siagian, Iyone E. T.; Ottay, Ronald I. (UNIVERSITAS SAM RATULANGI, 2016)
Woman is one of the potential resourches owned by Indonesia, whose strength is not only can play a role in filling the development in various areas, but can also bring Indonesia into one of the bigger, powerful, and independent country. Violence against women is already became public attention, because in society that is already built on the principles of rationality, humanism, democracy, the culture of violence is increasing. The importance of knowledge and public awareness about violence against women is needed to prevent the occurrence of the phenomenon of iceberg in the development of that case. This study is aimed to find out the description of knowledge about violence against women and the prevention at GMIM Viadolorosa Manado, during September 2016 untul November 2016. A descriptive study with interviews and focus group discussions methods. The result shows that the informant’ knowledge regarding violence against women affected by observation of the environtment and the mass media (3 of 4 informant) and the knowledge about violence prevention in women affected by the scope of the work. Keywords: Violence, Woman, Pastor